Spatial arrangement of casein micelles and whey protein aggregate in acid gels: Insight on mechanisms. (October 2015) - Andoyo, Robi; Guyomarc'h, Fanny; Burel, Agnes; Famelart, Marie-Hélène
Abstract: Skim milk used for the yoghurt manufacture contains 2 main colloidal particles, the native micellar casein (NMC) and the heat-induced whey protein aggregates (WPA). The aim of this study was to understand how these 2 colloids organize in space to form binary acid gels. While acid milk gels were considered homogeneous for scales typically above ∼10 μm, shorter length scales were examined to investigate the early stages of particle aggregation. The NMC and WPA were dispersed in milk permeate at different protein concentrations, separately or in an 80/20 w/w mixture (MIX). Acidification was performed at 35 °C with glucono-δ-lactone to achieve a final pH at ∼4.5 in 6 h. Acid gelation was studied by rheology, while the microstructure of the gels at pH 4.5 was studied by confocal scanning laser microscopy and transmission electron microscopy (TEM). Using Shih et al.'s (1990) model on the rheological data, it seemed that aggregation in the NMC and MIX mixtures was driven by the casein micelles and therefore differed from that of the WPA suspension. The different organizations were confirmed using image analysis of confocal or TEM images. The differences in gel formation were discussed in terms of the different interactive properties of the surface of these 2 colloids, together with their different internal structure. Graphical abstract: Highlights: Acid gels were made from casein micelles (NMC) and whey protein aggregates (WPA). Acid gels were made from 80/20 mixtures of NMC and WPA, respectively. Fractal dimension ( D f ) of gel flocs were determined by rheology and image analysis. Replacement of 20% NMC by WPA hardly changes the D f value of the flocs. Aggregation in the NMC and MIX mixtures was driven by the casein micelles.